Notes on the modernization of the General Sales Tax regime in Peru within the framework of digital economy: the experience of the European Community and the underdeveloped Peruvian regime - Zegarra Camarena, Rocío (2019)
This article approaches the treatment of Value-Added Tax applicable to digital transactions in the European Union and Peru. In this regard, it is noted that, although Peru was one of the first jurisdictions in Latin America to face the challenges of digitalization of the economy in the field of Income Tax, over time these efforts have become outdated. For this reason, after reviewing the main aspects and scope of the Peruvian Value-Added Tax and General Sales Tax regime, the author proposes some ideas to update them, based on the reflection of the European experience and its regulation on digital transactions.